2016
DOI: 10.1016/j.fbj.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the relationship between inventory management and firm performance: An organizational life cycle perspective

Abstract: Existing evidence regarding inventory-performance relationship is inconclusive. A perspective that this paper stresses in considering this relationship is that it might depend on organizational life cycle stage. The underlying assumptions of this argument are that organization's strategies and relationships vary with its life cycle stage, organizations develop their own strategies to fit between inventory system and organizational settings, and design of inventory system is not a linear process, rather it is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 85 publications
1
37
1
1
Order By: Relevance
“…Obtaining further evidence regarding this issue may help in understanding the dynamics of inventory-performance relationship as SMEs have not only some unique characteristics that differentiate them from larger firms, but also a higher failure rate as compared to the larger firms (Elsayed and Wahba, 2016). Furthermore, the existing evidence regarding inventory-performance relationship is still inconclusive (Elsayed and Wahba, 2016). Thus, this study rectifies the deficiency by providing evidence on IMPs in the micro retailing sector and a further investigation through the incorporation of knowledge of IMPs as the mediating variable on IMPsperformance link.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining further evidence regarding this issue may help in understanding the dynamics of inventory-performance relationship as SMEs have not only some unique characteristics that differentiate them from larger firms, but also a higher failure rate as compared to the larger firms (Elsayed and Wahba, 2016). Furthermore, the existing evidence regarding inventory-performance relationship is still inconclusive (Elsayed and Wahba, 2016). Thus, this study rectifies the deficiency by providing evidence on IMPs in the micro retailing sector and a further investigation through the incorporation of knowledge of IMPs as the mediating variable on IMPsperformance link.…”
Section: Introductionmentioning
confidence: 99%
“…Panigrahi (2013) indicated that inventory conversion period had an inverse relationship with the firms' profitability i.e., when the inventory conversion period (ICP) days increases, the profitability of the firm decreases, and vice versa. Next, Elsayed and Wahba (2016) found that while inventory to sales ratio affected organisation's performance negatively in the initial growth stage and the maturity stage, it exerted a positive and significant coefficient on performance in either the rapid growth stage or the revival stage. Jonsson and Mattsson (2008) concluded that the way of determining and the review frequency of safety stocks and lead times had great importance for the planning performance of MRP methods, while the determination and review of order points, review frequencies and run-out times were important for re-order point methods.…”
mentioning
confidence: 99%
“…Furthermore, the Akaike information criterion (AIC) (Akaike, 1974(Akaike, , 1987) is utilized to identify the sample's best number of firm life cycle phases. Following the research done by Elsayed and Wahba (2016), we used a one-way ANOVA and a T-test for each clustering variable (dependent variable) and firm life cycle stage (independent variable). As indicated in Tables 3-8, the F-statistics from ANOVA and the t-value from the T-test demonstrate significant differences in the means for the four clustering variables (firm age, assets growth, sales growth, and capital intensity).…”
Section: Cluster Analysismentioning
confidence: 99%
“…Estudos anteriores (Elsayed & Wahba, 2016;Gill et al, 2019;Kroes & Manikas, 2014;Shah & Shin, 2007), que abordam a questão de estoque e desempenho consideram diferentes graus de importância ao ambiente especifico do setor. Portanto, este estudo refinou a amostra para incluir apenas empresas que apresentavam relação significante entre estoque e receita.…”
Section: Amostra E Dadosunclassified